KEDUDUKAN TERTANGGUNG DALAM ASURANSI JIWA KREDIT - Rahmat Adam; Saiful Anwar (Legal Standing : Jurnal Ilmu Hukum, 2021)
The position of the insured credit life insurance in the bank that handles the insurance company as the insurer and the banking company as the policy holder, which provides credit and terms that require a balanced and direct relationship. This is important, because the different interests of this large industry are related to the insured. For this reason, the insured credit life insurance company needs legal protection with special arrangements, which are based on existing norms. In addition, the interests of the two industries as insurers and policyholders need synergy. interest in credit management for each.